2011
DOI: 10.1007/s11060-011-0689-z
|View full text |Cite|
|
Sign up to set email alerts
|

Oxcarbazepine monotherapy in patients with brain tumor-related epilepsy: open-label pilot study for assessing the efficacy, tolerability and impact on quality of life

Abstract: We conducted a prospective, observational study to verify the efficacy, tolerability and impact on quality of life, mood and global neurocognitive performances of oxcarbazepine monotherapy in patients with brain tumor-related epilepsy (BTRE). Patients were followed for 12 months. We recruited 25 patients (11 females 14 males; mean age 49.7) affected with BTRE (17 de novo patients and 7 in monotherapy with other antiepileptics) and introduced oxcarbazepine monotherapy because of uncontrolled seizures and/or sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 31 publications
0
18
0
4
Order By: Relevance
“…29 A number of uncontrolled cohort studies, that measured depressive symptoms as secondary outcomes on rating scales, provide limited evidence in favour of methylphenidate 25,30 , oxcarbazapine 31 , bupropion SR 32 , gingko biloba 33 and donepezil 27 . It remains unknown whether any of these treatments are effective for clinically significant depressive disorder, or indeed any better than placebo.…”
Section: Mood and Behavioural Disordersmentioning
confidence: 99%
“…29 A number of uncontrolled cohort studies, that measured depressive symptoms as secondary outcomes on rating scales, provide limited evidence in favour of methylphenidate 25,30 , oxcarbazapine 31 , bupropion SR 32 , gingko biloba 33 and donepezil 27 . It remains unknown whether any of these treatments are effective for clinically significant depressive disorder, or indeed any better than placebo.…”
Section: Mood and Behavioural Disordersmentioning
confidence: 99%
“…45,46 The risk of severe skin toxicity is increased when patients are treated with phenytoin or carbamazepine or oxcarbazepine not only in combination with procarbazine, but also with radiotherapy. 47 Finally, EI-AED decrease the bioavailability of steroids, necessitating careful clinical monitoring when EI-AED are newly introduced in steroid-dependent brain tumor patients. Conversely, when EI-AED are replaced by non-EI-AED, it should be assessed whether steroid doses can be lowered.…”
Section: Interactions Of Cancer Therapy and Aed: Tolerabilitymentioning
confidence: 99%
“…Table 2 summarizes studies identified which have a focus on intellectual disability. [16], [17], [18], [20]] whilst other studies showed no or little improvement [ [35], [82], [85] ] .…”
Section: Summary Of Studies With a Focus On Intellectual Disabilitymentioning
confidence: 99%